THE IMPACT OF USING CANVA AS MEDIA IN TEACHING NATURAL SCIENCE FIELD TO THE FIFTH GRADE STUDENTS OF SD NEGERI PUCOK LUPU KABUPATEN PIDIE - Salminawati; Siti Mayang; Akmaluddin; Mhd Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research aims to find out if there is a significance difference between the students who are taught science natural field by using canva and the students who are taught science natural field without using canva. This research is conducted by using quantitative research. The design used in this research is quasi experiment. In this design, experimental group is given treatment meanwhile control group is not given treatment. This treatment is made for experiment to determine the effects of a given treatment. The population of this study is the fifth-grade students of SD Negeri Pucok Lupu in academic year 2022/2023. The total population is 52 students who were composed of two classes; class VA and class VB . Since there were only two classes of the fifth-grade students thus they were taken as the sample of this research and the students of class VB as experiment group meanwhile the students of class VA as control group. The data gotten were analyzed by using Mann-Whitney test. The result of Mann-Whitney test shows that Sig. (2-tailed) value of Mann-Whitney U test is 0.000. It means teaching natural science field to the fifth-grade students of SD Negeri Pucok Pulu by applying canva as media is successful to increase the students’ ability in mastering the subject.